Training of NBC Reconnaissance Specialists for Special Tasks Performance - O. V. Boltykov; I. A. Sazonov; A. O. Smirnov (Вестник войск РХБ защиты, 2021)
Combat training is the main content of the daily activities of commanders (chiefs), command and control bodies (headquarters) and troops. The purpose of this work is to summarize the experience of training of NBC reconnaissance specialists, obtained during the training of NBC reconnaissance specialists in the period from December 2018 to March 2020 on the basis of military units of the Shikhany garrison. The main forms of this training were lectures, practical and control exercises in military-political, special, fire, technical, military-medical training, in NBC protection, driving, military topography and communications training. The personnel received practical skills in identifying hazardous chemicals, explosives and toxic chemicals simulators with chemical reconnaissance and chemical control devices.